TIA Chatbot: Transient Ischemic Attack Chatbot - Mohd Sabri, Mohammad Zaim Teh (IRC, 2019)
Every hospital and clinic have their own procedure to conduct medical checkup and some medical check-up are costly. This could affect the citizen from getting any medical check-up. Every doctor has concern towards their patient health condition and there are also ways for the doctor to inform on the condition of the patient itself whether it is good or bad. By developing this project, it is beneficial in terms of citizens perspective because it provides the necessary information towards their enquiries which concern to stroke matters. This project is expected to provide accuracy on information and details provided regarding on the issues and efficiency during the user interaction for the user to receive better recommendation on their current issues through a Chatbot which an interactive communication bot.